Is there any alternative to traditional food frequency questionnaire for evaluating habitual dietary intake? - Luis M. Béjar (Nutrición Hospitalaria, 2017)
Introduction: Dietary assessment methods are an important instrument for nutrition research . Food frequency questionnaires (FFQs) have been the most frequently used dietary assessment tool in epidemiological and intervention studies. There is a great necessity for new methods of determination of habitual dietary intake that overcome the limitations of these traditional methods. Objectives: The objectives of the present study were to develop a new method, based on an application for mobile phones called e-EPIDEMI- OLOGY, designed to record individual consumption data about a short series of foods/drinks, and to compare data collected using this tool with those obtained from a previously validated short paper FFQ. Methods: University students over 18 years recorded the consumption of certain foods/drinks using e-EPIDEMIOLOGY during 28 consecutive days and then fi lled out a short paper FFQ at the end of the study period. To evaluate the agreement between both methods, Spearman’s correlation coeffi cient, cross-classifi cation analysis and a weighted kappa statistic were used. Results: One hundred and nineteen participants completed the study (71.4% female and 28.6% male). The mean Spearman’s correlation coef- fi cients for food/drink group intake between the two methods was 0.73. The mean percentage of participants cross-classifi ed into categories of “exact agreement + adjacent” was 91.6%. The average weighted kappa statistic was 0.60. Conclusions: The results indicate that e-EPIDEMIOLOGY has good agreement with the previously validated FFQ short paper. However, it was noted that further testing of e-EPIDEMIOLOGY is required to establish its wider utility.